Assessment of Observed and Self-Perceived Information Literacy in Compulsory Secondary Education Students From a Spanish Region With a High Performance in PISA - García-Llorente, Héctor Javier (2020)
This research aims to assess the self-perceived level and the actual level of information literacy among Compulsory Secondary Education students. Two questionnaires were administered to a sample conformed by 1422 students between the ages of 14 and 17, from Castilla and León, a Spanish region with high academic performance (Junta de Castilla y León, 2015). The tools for the collection of data are divided into the four dimensions of information literacy: Research, Assessment, Management, and Communication. The results show that the students have a high level of self-perceived skills (average score 3.14 of a 0-4 scale), especially those related to the Communication dimension. However, the level of demonstrated competence is noticeably below the self-perceived level, with the exception of the Communication dimension (average score 2.40 of a 0-4 scale). In conclusion, the evidence shows a need for specific training in information literacy skills, mainly related to the Research and Assessment dimensions, among ninth and tenth graders of this region.